‘A VERY LAZY DEER’: REVISION OF THE COTYPE OF NOTHROPUS CARCARANENSIS (MAMMALIA, XENARTHRA) (Ameghiniana, 2020)
Here it is reviewed the specimen MACN-Pv 12630, the cotype of the ground-sloth Nothrophus cararanensis Bordas, 1942, and proposed that it should be taxonomically relocated to the extinct deer Morenelaphus. The specimen in question is represented by a fragmentary braincase, that shares several features with Cervidae and, more detailed with Morenelaphus. Besides antler morphology, this contribution shows that basicranium attributes are also very important to elucidate taxonomical affinities within South American Cervidae.